A historical Greek reader : Mycenaean to the Koiné (Oxford University Press, 2010)
Designed to be used as a textbook in university courses (either upper-level undergraduate or postgraduate), A Historical Greek Reader will also serve as a reference tool for researchers. It provides an introduction to the history of the ancient Greek language, and to Indo-European and historical linguistics in general. - ;A Historical Greek Reader provides an introduction to the history of the ancient Greek language by means of a series of texts with linguistic commentary, cross-referenced to each other and to a reference grammar at the front. It offers a selection of epigraphic and literary t